The Tower is Falling: Collapse, Connection, and the Possibility of Reorientation - Hugh Palmer (Murmurations, 2025)
This paper uses the Tarot arc of the Devil, the Tower, the Star, and the Fool to explore systemic collapse and the logics of masculinised power. Drawing on archetypal imagery, ecological systems theory, posthumanist feminism, and lived experience, it argues that the panmorphic crisis (Simon, 2021) of climate change, technological acceleration, and political instability are not merely failures of implementation. They reflect a deeper failure of imagination. The Tower is falling because it was built on the ideology of the Devil, to deny relationship, vulnerability, and feedback.  In its place, the Star offers a different kind of intelligence: attentive, embodied, and quietly relational. Figures such as Trump and Musk are read not as aberrations but as expressions of a system that rewards shamelessness and disconnection. The paper invites readers into an ethic of reorientation, recognising even those we most oppose as part of our systemic kin. The Fool, traditionally male, is reclaimed as a post-binary, post-certainty figure who gestures toward a different way of going on, a journey that is uncertain, attentive, and deeply relational.